2014
DOI: 10.7182/pit2014384
|View full text |Cite
|
Sign up to set email alerts
|

Preservation of Kidneys by Machine Perfusion Influences Gene Expression and May Limit Ischemia/Reperfusion Injury

Abstract: Mean expression levels of hypoxia-inducible factor-1α were significantly higher in the cold storage groups, and lower in the machine perfusion and living-related donor groups. Five-year graft survival was significantly (P< .05) lower in the expanded criteria donor-cold storage group (66%) than in the standard criteria donor-machine perfusion group (90%). Machine perfusion influences gene expression related to hypoxia during reperfusion and may improve the long-term results of kidney transplant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 34 publications
(36 reference statements)
0
13
0
Order By: Relevance
“…45). Furthermore, its protective effects have been extensively described in diverse forms of extra-renal tissue damage (e.g., brain, liver, heart, organ transplantation) (4652). However, less certain than the existence of HO’s protective actions is the exact mechanism by which that protection is effected.…”
Section: Discussionmentioning
confidence: 99%
“…45). Furthermore, its protective effects have been extensively described in diverse forms of extra-renal tissue damage (e.g., brain, liver, heart, organ transplantation) (4652). However, less certain than the existence of HO’s protective actions is the exact mechanism by which that protection is effected.…”
Section: Discussionmentioning
confidence: 99%
“…1 The donor organ undergoes a number of injurious insults prior to, and during the early post-operative phase that are thought to contribute to the later development of chronic rejection. 2, 3 One such insult is ischemia reperfusion injury (IRI). 4 IRI is an unavoidable complication in the process of cardiac transplantation, with the donor heart rendered ischemic for prolonged periods prior to implantation into the recipient and subsequent reperfusion.…”
Section: Introductionmentioning
confidence: 99%
“…Extracellular oxygen carriers may logistically, rheologically, and immunologically be superior to packed red blood cells, but need further investigation. Studies on human DCD and ECD kidneys supported the superiority of HMP over SCS (32,43,45,46). Reznik et al (43) found a considerably lower number of complications and negative effects, like acute rejection, correlated with HMP kidneys retrieved from DCD donors.…”
Section: Hypothermic Machine Perfusion Techniquesmentioning
confidence: 96%